Reversible Quadruple Switching with Optical, Chiroptical, Helicity, and Macropattern in Self‐Assembled Spiropyran Gels. (29th May 2017) - Miao, Wangen; Wang, Sheng; Liu, Minghua
Abstract : Enantiomeric glutamate gelators containing a spiropyran moiety are designed and found to self‐assemble into a nanohelix through gelation. Upon alternating UV and visible light irradiation, the spiropyran experiences a reversible change between a blue zwitterionic merocyanine state and a colorless closed ring state spiropyran in supramolecular gels. This photochromic switch causes a series of subsequent changes in the optical, chiroptical, morphological properties from supramolecular to macroscopic levels. While the solution of the gelator molecules does not show any circular dichroism (CD) signal in the region of 250–700 nm due to the fact that the chromophore is far from the chiral center, the gel shows chiroptical signals such as CD and circularly polarized luminescence (CPL) because of the chirality transfer by the self‐assembly. These signals are reversible upon alternating UV/vis irradiation. Therefore, a quadruple optical and chiroptical switch is developed successfully. During such process, the self‐assembled nanostructures from the enantiomeric supramolecular gels also undergo a reversible change between helices and fibers under the alternating UV and visible light trigger. Furthermore, a rewritable material fabricated from their xerogels on a glass is developed. Such rewritable material can be efficiently printed over 30 cycles without significant loss in contrast and resolution using UV and visible light. Abstract : A reversible quadruple optical and chiroptical switch that is responsive to photochromism, fluorescence, chiroptics, and circularly polarized luminescence (CPL) is developed based on the enantiomeric spiropyran gels. It responds to stimuli of alternating UV and visible light. Moreover, the xerogels can be fabricated as rewritable materials.